Mining Our Lives for the Diamonds - Wesley-Esquimaux, Cynthia (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Aboriginal women across Canada have waited far too patiently for wrongs to be righted and senseless historic and contemporary pain to cease. Today, through narratives like this one, we are undertaking a heroic journey, a journey that begins with truth; in fact, it is a journey that begins with the laying down of seven profound Indigenous values, values that are stepping stones to an ancestral home some of us have never visited in our entire lives. This means the gathering up of a collective courage, a willingness to begin, to step out and into what we know to be true and waiting for release. So, this is my story, a story that begins like many others…once upon a time